Relation between stress and gastrointestinal disorders - Gurung, Ankita; Srivastava, Rani; Kumar, Ashok; Debapriya (International Journal of Research in Medical Sciences, 2025)
Background: This study investigated psychological influences in gastrointestinal (GI) disorders by analyzing relationships among stress, depression, anxiety, and somatization. Standardized scales were applied with 73 participants, revealing notable associations between stress and physical complaints. Findings highlight the significance of the brain-gut connection and recommend integrative therapeutic approaches. Aim was to evaluate the association between stress levels and general health, somatization, depression, anxiety, and illness perception among patients with gastrointestinal disorders. Methods: This cross-sectional survey-based research distributed offline questionnaires to patients experiencing gastrointestinal symptoms to assess stress and its associations with general health, somatization, depression, anxiety, and illness perception. Data collection employed four standardized instruments: GHQ-12, SDC, DASS-42, and IPQ-R. Data were processed with Microsoft Excel and SPSS version 23, emphasizing descriptive and inferential methods. Descriptive analysis involved calculating mean and standard deviation for GHQ-12, SDC, DASS-42, and IPQ-R. Results: Of 73 respondents, SDC showed 6.8% had marked somatic concerns. These findings emphasize the overlap between psychological stress and physical outcomes, as patients with GI symptoms often present emotional struggles through somatic complaints. Conclusions: Stress was significantly correlated with the somatization disorder checklist (GI).